2013
DOI: 10.5935/1808-8694.20130136
|View full text |Cite
|
Sign up to set email alerts
|

The impact of speech rate on sentence recognition by elderly individuals

Abstract: regardless of their peripheral hearing, the elderly subjects included in this study were more able to recognize speech when sentences were played at a slower rate against a quiet background. When sentences were played against a noisy background, the elderly subjects with hearing loss had more significant performance improvements than the ones with normal hearing when sentences were played at a slower rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 18 publications
0
9
0
7
Order By: Relevance
“…In recent years, the SLP-BR test proved to be very versatile for research purposes (7,8,9,10) and have different goals and strategies of implementation, hence it can be used in various ways, according to the objective of raters. Therefore, a decision was made to develop the new proposal.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the SLP-BR test proved to be very versatile for research purposes (7,8,9,10) and have different goals and strategies of implementation, hence it can be used in various ways, according to the objective of raters. Therefore, a decision was made to develop the new proposal.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of reaching the best way to evaluate temporal resolution auditory skill is highlighted, as it is closely related to speech intelligibility 36 , being responsible for distinguishing or resolving sound stimuli 37 . A valuable guideline that should be given to the elderly or their caregiver is that it is not always necessary to speak stronger, since it is pointed out 38 that, regardless of the peripheral condition, message recognition is facilitated when speech is performed at a slower speed and in silence. Table 3 also shows the reference values for MLD, the averages found for the group of elderly with normal thresholds and those with hearing loss, are close.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding speech is one of the most important elements in human communication, and this is the reason why the use of sentences is considered the most accurate instrument to assess the communication of individuals, because their performance before sentences will provide results of everyday speech situations (8,12,21) . Habitual speech situations are typically associated with presence of competitive noise, and this aspect is also one of the complaints most frequently mentioned by older individuals (23) .…”
Section: Discussion On Speech Intelligibility Index (Sii) and Speech Perception In The Presence Of Competitive Noisementioning
confidence: 99%
“…Studies (3,7,8) have demonstrated that a common complaint among the elderly population refers to the difficulty in understanding speech in presence of competitive noise. When difficulty in understanding speech is observed, especially in noise, it is suggested that temporal processing is in decline (7) .…”
Section: Discussion On Speech Intelligibility Index (Sii) and Speech Perception In The Presence Of Competitive Noisementioning
confidence: 99%
See 1 more Smart Citation